KEMAMPUAN PENGGUNAAN HURUF KAPITAL DALAM MENULIS KARANGAN BERDASARKAN POKOK PIKIRAN PESERTA DIDIK KELAS V SDN BALUNGKIDUL 02 JEMBER - Anggun Indah Saputri; Hari Satrijono; Zetti Finali (Jurnal Muassis Pendidikan Dasar, 2022)
The purpose of this study was to describe, to determine the factors that influence, and to find out the efforts to increase the ability to use capital letters for fifth grade students at SDN Balungkidul 02 Jember in writing essays based on the main idea. This research uses interview and documentation method. The results and conclusions of this study is that the average value of the ability to use capital letters is 9 or 33% belonging to the sufficient category. These results are influenced by factors of student interest in reading, use of learning tools and media, encouragement from parents and the level of intelligence of students. Furthermore, efforts were made to improve by means of teachers using multimethods in learning, teachers guiding students gradually, teachers providing motivation and encouragement to students, and the family environment providing motivation and encouragement for students